Neonatal sepsis in low-income countries: epidemiology, diagnosis and prevention. Issue 5 (3rd May 2020) - Popescu, Constantin Radu; Cavanagh, Miranda M. M.; Tembo, Bentry; Chiume, Msandeni; Lufesi, Norman; Goldfarb, David M.; Kissoon, Niranjan; Lavoie, Pascal M.
ABSTRACT: Introduction : Sepsis accounts for up to one-third of neonatal deaths in the world each year. The World Health Organization acknowledges neonatal sepsis as a major global health concern, and that the highest burden occurs in low- and middle-income countries (LMICs). Despite major research and clinical progress in this area, we still lack accurate diagnostic tools for neonatal sepsis, complicating the management of this condition. Areas covered : The purpose here is to review the latest data on the incidence, diagnosis, prevention, and management of neonatal sepsis in LMIC. We discuss the limitations of current diagnostic tests – including their lack of availability – and how this may influence global estimates of cases. We review the benefits of antenatal, intrapartum, and post-natal preventive measures. We briefly discuss the management, highlighting the emergence of antimicrobial resistance. Finally, we expose some high priority areas. Expert opinion : Neonatal sepsis is a challenging condition requiring a multifaceted approach to address the major diagnostic issues, but also the underlying socio-economic causes that nourish epidemic cases in LMIC. Focusing on antibiotics as a main pillar of intervention is likely to engender antimicrobial resistance, eventually hindering the appreciable gains LMICs have achieved in neonatal health outcomes.